2019
DOI: 10.1111/1346-8138.14935
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of long‐term treatment with efinaconazole 10% solution in patients with onychomycosis, including severe cases: A multicenter, single‐arm study

Abstract: We evaluated the efficacy of efinaconazole 10% topical solution in long‐term use, for up to 72 weeks, for onychomycosis, including severe cases. Among 605 participants, 219 patients diagnosed as having onychomycosis were evaluated for the efficacy of efinaconazole. The treatment success rate (<10% clinical involvement of the target toenail) at the final assessment time point was 56.6%, the complete cure rate was 31.1% and the mycological cure rate was 61.6%, all of which increased over time, demonstrating that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…To evaluate the efficacy and safety of long‐term use (up to 72 weeks), a single‐arm open study ( n = 219) including severe cases (>50% affected nail area) was conducted in Japan 71 . According to the report, at week 72 the complete cure rate was 31.1%, mycological cure rate was 61.6% and treatment success (<10% clinical involvement of the target nail) was 56.6% 71 . The results of these studies demonstrated that continuous application contributed to the improvement of the cure rate.…”
Section: Cq3: Is Topical Efinaconazole 10% Solution Recommended For Tinea Unguium Treatment?mentioning
confidence: 99%
“…To evaluate the efficacy and safety of long‐term use (up to 72 weeks), a single‐arm open study ( n = 219) including severe cases (>50% affected nail area) was conducted in Japan 71 . According to the report, at week 72 the complete cure rate was 31.1%, mycological cure rate was 61.6% and treatment success (<10% clinical involvement of the target nail) was 56.6% 71 . The results of these studies demonstrated that continuous application contributed to the improvement of the cure rate.…”
Section: Cq3: Is Topical Efinaconazole 10% Solution Recommended For Tinea Unguium Treatment?mentioning
confidence: 99%
“…In the last years, the new antifungal agent efinaconazole (EFI), a triazole drug that inhibits fungal lanosterol 14 α-demethylase involved in the biosynthesis of ergosterol, has been introduced in the market for the treatment of onychomycosis. EFI displays a broad spectrum of in vitro activity against dermatophytes, nondermatophyte molds, and yeasts, showing a more potent antimicrobial activity than the currently marketed antifungal agents (810).…”
Section: Introductionmentioning
confidence: 99%
“…For itraconazole pulse therapy (400 mg/day), the clinical and complete cure rates at 72 weeks with 3 courses were 31.8% and 23.4%, respectively, and 32.1% and 25.9% (28/108), respectively, for 4 courses [20]. The reported complete cure rate with topical agents is approximately 30-40%, and a long period of administration is required for achieving complete cure [8][9][10]. In terms of the complete cure rate, our study achieved excellent results.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2010, two topical antifungal agents, e naconazole 10% solution and luliconazole 5% solution, have been approved for the treatment of onychomycosis in Japan. Compared with systemic therapy, topical agents are not associated with serious adverse events and can be applied safely, but they are not as effective as systemic therapies [8][9][10]. In addition, complete cure can take considerable time [10].…”
Section: Introductionmentioning
confidence: 99%